Evaluating cardiovascular risk in an Inclusion Health population admitted to secondary care - Gao, Yujia; Norman, James (Frontiers in Cardiovascular Medicine, 2025)
IntroductionInclusion Health (IH) encompasses individuals facing social exclusion, presenting a myriad of risk factors leading to compromised health. IH populations, including homeless individuals, substance abusers, and vulnerable migrants, have higher disease prevalence, earlier mortality, and more barriers to healthcare access, with increased risks of developing cardiovascular diseases. While QRISK3 is a validated tool for predicting ten-year cardiovascular risks in the general population in primary care, its application in secondary care or IH populations remains underexplored.MethodsThis prospective study, conducted at University College London Hospital (UCLH) between December 2021 and December 2023, evaluated IH patients using a locally-developed Collaborative Holistic Inclusion Health Patient Assessment (CHIPA) tool, incorporating clinical scoring systems including QRISK3. QRISK3 scores and corresponding Q ages were calculated independently using its online platform, based on patient demographics, cardiovascular histories, and cholesterol levels. The CHIPA was a detailed medical and social history questionnaire used to evaluate the IH patients referred to IHT in a consistent manner, including the incorporation of questions related to QRISK3 and other scoring systems.ResultsA total of 217 IH individuals were included in this study (median: 48 years; range: 25-81 years). Our IH patient cohort exhibited significantly higher QRISK3 scores compared to the general population (p < 0.001, paired Wilcoxon test), ranging from 0.1% to 81.7%, with an average increase of 8.6%. The corresponding Q age was, on average, 13 years older than patients' actual age, with a median of 62 years, and 35% of patients had a positive cardiovascular history. The relative risk ranged from 0.5 to 78.0, with an average of 4.0. Compared with the general population, IH patients demonstrated elevated cardiovascular risk.DiscussionWe highlight the utility of QRISK3 and CHIPA tools in early cardiovascular risk identification within the Inclusion Health cohort of patients, facilitating timely interventions. Integrating clinical risk scores into holistic assessments can improve referral practices, potentially enhancing overall health outcomes and reducing mortality in IH patients.